APLIKASI TRICHOKOMPOS DAN PUPUK GRAND-K TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L) PADA LAHAN GAMBUT RAWAN TERENDAM - Selvia Sutriana; Saripah Ulpah; M Nur (Jurnal Agroteknologi, 2021)
Riau is a province in Sumatra Island with the widest peatland covering up to ± 4,04 million Ha or about 56,1% of the area, with various type of peat, including the potentially submerged peat area.  With the peat charasteristics drawbacks such as low nutrient content and relatively high acidity, cause this type of land  barely cultivated for horticulture crop such as shallot. Whilst, in Indonesia, shallot is part of daily society culinary component. Therefore, efforts are needed to make use of peat land for this type of commodity by overcoming the shortages, for example by applying Trichocompost combined with Grand-K fertilizer. This research thus aimed at evaluating the growth and yield of shallot in potentially submerged peat soil, treated with Trichocompost and Grand-K Fertilizer. Experiment was conducted on peat soil   in Labersa Street Kelurahan Simpang tiga Kecamatan Bukit Raya Kota Pekanbaru for three months, from October to December 2019. The experiment was arranged in completely factorial design with two factors; each at four levels. The factors were Trichocompost (at 0, 2, 4, 6 ton ha-1) and Grand K fertilizer (at  0, 50, 100, 150 kg ha-1). The parameters observed were the percentage of seed viability, plant height, number of leaf, number of tuber, and the yield per plan. Results of the experiment showed that the best combination of treatment was Trichokompos at 4 – 6 ton ha-1 dan Grand K at 150 kg ha-1.